2016
DOI: 10.1111/bjdp.12152
|View full text |Cite
|
Sign up to set email alerts
|

Development of category formation for faces differing by age in 9‐ to 12‐month‐olds: An effect of experience with infant faces

Abstract: We examined category formation for faces differing in age in 9- and 12-month-olds, and the influence of exposure to infant faces on such ability. Infants were familiarized with adult or infant faces, and then tested with a novel exemplar from the familiarized category paired with a novel exemplar from a novel category (Experiment 1). Both age groups formed discrete categories of adult and infant faces, but exposure to infant faces in everyday life did not modulate performance. The same task was conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 58 publications
3
13
0
Order By: Relevance
“…In addition, younger infants (i.e., 3-month-olds) discriminate among familiar adult faces, and among less familiar infant faces, whereas older infants (i.e., 9-to 10-month-olds) continue to discriminate adult faces, but show difficulty discriminating among infant faces (Cassia, Bulf, Quadrelli, & Proietti, 2014). Also, infants between 9 and 12 months of age come to form different categories for adult, child, and infant faces (Damon, Quinn, Heron-Delaney, Lee, & Pascalis, 2016). Finally, with regard to selective learning, children favor adults over peers (Rakoczy, Hamann, Warneken, & Tomasello, 2010).…”
Section: Face Processing In Infancy 34mentioning
confidence: 99%
“…In addition, younger infants (i.e., 3-month-olds) discriminate among familiar adult faces, and among less familiar infant faces, whereas older infants (i.e., 9-to 10-month-olds) continue to discriminate adult faces, but show difficulty discriminating among infant faces (Cassia, Bulf, Quadrelli, & Proietti, 2014). Also, infants between 9 and 12 months of age come to form different categories for adult, child, and infant faces (Damon, Quinn, Heron-Delaney, Lee, & Pascalis, 2016). Finally, with regard to selective learning, children favor adults over peers (Rakoczy, Hamann, Warneken, & Tomasello, 2010).…”
Section: Face Processing In Infancy 34mentioning
confidence: 99%
“…A recent study showed that both adults and children evinced this so-called other-race categorization advantage [ 25 ]. And indeed, a second line of evidence consistent with this hypothesis derives from the handful of studies assessing infants’ social categorization capacities [e.g., 26 , 27on gender; 28on age; and 29 , 30on race]. Especially pertinent to the present hypothesis, studies found that infants tend to show an asymmetry in categorizing familiar vs. unfamiliar categories [see 27on gender, 28on age].…”
Section: Introductionmentioning
confidence: 54%
“…And indeed, a second line of evidence consistent with this hypothesis derives from the handful of studies assessing infants’ social categorization capacities [e.g., 26 , 27on gender; 28on age; and 29 , 30on race]. Especially pertinent to the present hypothesis, studies found that infants tend to show an asymmetry in categorizing familiar vs. unfamiliar categories [see 27on gender, 28on age]. Particularly in regard to race, 6-month-old Caucasian infants looked longer at a Caucasian face after being familiarized to Asian faces, but did not look longer at an Asian face after being familiarized to Caucasian faces [ 29 , see also 30 ].…”
Section: Introductionmentioning
confidence: 97%
“…Further research has investigated infant ability to categorize differently aged faces. Nine‐ and 12‐month‐olds have provided evidence of forming distinct categories of adult and infant faces, demonstrated in a visual familiarization/novelty‐preference paradigm (Damon et al, ). Twelve‐month‐olds also formed distinct categories of child and infant faces; however, 9‐month‐olds only formed a category of child faces, which excluded infant faces, but not the reverse.…”
Section: Introductionmentioning
confidence: 99%
“…These attributes include age, gender, and race (e.g., Damon, Quinn, Heron-Delaney, Lee, & Pascalis, 2016; Kelly et al, 2007; Quinn, Yahr, Kuhn, Slater, & Pascalis, 2002) and are generally thought not to be processed independently (but see Bruce & Young, 1986). Instead, multiple dimensions may interact (e.g., Macchi Cassia, Luo, Pisacane, Li, & Lee, 2014b; Quinn et al, 2008).…”
mentioning
confidence: 99%